Peningkatan Pengamanan di Area Landasan Pacu Bandar Udara Domine Eduard Osok Sorong - Irfan (Politeknik Penerbangan Makassar, 2019)
Every person is prohibited from being in certain areas in the airport, making obstacles, and carrying out other activities in the area of ​​flight operational safety that can endanger the safety and security of aviation unless obtaining permission from the airport authority. In this case, the particular area in question is the runway. The movement of people who cross the runway is an example of a case that is often found and there is no aviation security post around runway 09, which usually residents cross the runway through that point. The security in the runway area that has not been optimal has resulted in disruptions to Air Traffic controller officers related to the provision of air traffic services. The purpose of the research is to improve safety around the runway area and create smoothness and comfort in air traffic services. This study uses qualitative research methods in observations about security around the runway area. The results of this study are expected to provide solutions to problems that occur related to the lack of security in the runway area which impacts the service performance of Air Traffic Controller officers can be minimized, especially during peak hours. It is recommended to the management of Domine Eduard Osok Sorong Airport to conduct socialization to residents around the runway area, erect a barrier/fence and add an avsec post around runway 09 where the place is a point where residents normally cross the runway.